Evaluation of the Use of Law Library among Legal Practitioners in Kwara State - Yahaya, Ibrahim Olarewaju; Ambali, Zainab Olanihun; Oyedokun, Tunde Toyese; Balogun, Tawakalitu Raufu (Universitas Pendidikan Indonesia, 2021)
The study evaluated the use of the library by legal practitioners in Kwara State. A descriptive survey was adopted, a simple random sampling technic was adopted for the sample selection of participants and the questionnaire serves as an instrument for data collection. A sample size of 257 participants was selected from the study population of 772 and only 252 copies of the questionnaire are returned and found useful, constituting a 98% returned rate. The study found that law reports, law textbooks, reference materials, index and abstracts, legal periodicals, legislation and statutes, and digests are the library resources available to legal practitioners. It was further reported that the majority of the respondents use legal periodicals, law reports, law textbooks, indexes and abstracts, legislation and statutes, and digest daily while the majority of them use reference materials only once in a month. The majority of the respondents purposely use library resources to further knowledge on legal issues; for work in progress; to keep informed of the development in the legal profession; to defend their client in the court of law, and for case preparation. The test hypothesis indicated that there is gender difference in male and female legal practitioners’ use of library resources in Kwara state. The reason for this is that the t-value is 84.961, and the associated p-value which is 0.000 less than the level of significance 0.05. Also, the mean score of male legal practitioners is significantly higher than the mean score of female legal practitioners, that is, the mean score of male legal practitioners is 37.190 compared to the mean score of female legal practitioners which is 28.832? The study, therefore, recommended that adequate provision should be made for current legal information resources in the library.